Pengaruh Independensi, Gaya Kepemimpinan, Komitmen Organisasi, Pegalaman Kerja, dan Pemahaman Good Governance pada Kinerja Auditor - Suryagita Apsari, Ni Nyoman; ., Gayatri (E-Jurnal Akuntansi; Vol 24 No 1 (2018), 2018)
The aims of the current study are to determine the effect of independence, leadership style, organization commitment, work experience, and comprehension of good governance towards performance of the auditor i n Inspectorate of Bali Province. The population of this study were all functional position auditor and all officials of local government affairs in Inspectorate of Bali Province and the sampling method was using saturated or census sample method. The numbers of samples used were 41 respondent s. The data were collected by questionnaire measured by likert scale. The result of the current study shows that independence, leadership style, organization commitment, work experience, and comprehension of good governance have a positive and significant impact on the performance of the auditor in Inspectorate of Bali Province. Keyword: independence, leadership style, organization commitment, work experience, comprehension of good governance, performance of the auditor.